Commensal microbiota modulates phenotypic characteristics and gene expression in piglet Peyer’s patches - Zhang, Jinwei; Shen, Yang; Yang, Guitao; Sun, Jing; Tang, Chuang; Liang, Hao; Ma, Jideng; Wu, Xiaoqian; Cao, Haoran; Wu, Meng; Ding, Yuchun; Li, Mingzhou; et al. (Frontiers in Physiology, 2023)
The gastrointestinal tract contains a complex microbial community. Peyer's patches (PPs) play an important role in inducing mucosal immune responses in the gastrointestinal tract. However, little is known about the effect of commensal microbiota on the host’s PPs. Here, we analyzed the phenotypic-to-transcriptome changes in the intestine PPs of specific pathogen-free (SPF) and germ-free (GF) piglets (fed in an environment with and without commensal microbiota, respectively) to elucidate the role of commensal microbiota in host intestine mucosal immunity. Analyses of anatomical and histological characteristics showed that commensal microbiota deficiency led to PP hypoplasia, especially regarding B and T cells. A total of 12,444 mRNAs were expressed in 12 libraries; 2,156 and 425 differentially expressed (DE) mRNAs were detected in the jejunal PP (JPP) and ileal PP (IPP), respectively (SPF vs. GF). The shared DE mRNAs of the JPP and IPP were mainly involved in basic physiological and metabolic processes, while the specific DE mRNAs were enriched in regulating immune cells in the JPP and microbial responses and cellular immunity in the IPP. Commensal microbiota significantly modulated the expression of genes related to B-cell functions, including activation, proliferation, differentiation, apoptosis, receptor signaling, germinal center formation, and IgA isotype class switching, particularly in the JPP. TLR4 pathway-related genes were induced in response to microbial colonization and in LPS/SCFA-treated B cells. We also detected 69 and 21 DE lncRNAs in the JPP and IPP, respectively, and four one-to-one lncRNA-mRNA pairs were identified. These findings might represent key regulatory axes for host intestine mucosal immunity development during microbial colonization. Overall, the findings of this study revealed that commensal microbiota modulated phenotypic characteristics and gene expression in the piglet intestine PPs and underscored the importance of early microbial colonization for host mucosal immunity development.